Linking Organizational Culture, Leadership Style, and Motivation to Employee Performance: A Strategic HRM Perspective - Kahar; A Nur Achsanuddin UA; Ismail Rasulong; Rahayu Japar (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the influence of motivation, organizational culture, and leadership style on employee performance within the context of PT Telekomunikasi Indonesia Tbk Witel Makassar. The objective is to understand how these human resource factors interact to shape individual productivity in a state-owned enterprise operating in a competitive and technologically dynamic sector. Employing a quantitative research design, data were collected through a structured questionnaire distributed to 92 employees, and analyzed using multiple linear regression to determine the significance and strength of the relationships among variables. The results reveal that motivation has the most substantial and statistically significant impact on employee performance, followed by organizational culture, while leadership style contributes positively but with weaker statistical relevance. These findings affirm that a performance management system centered on motivational drivers and culturally aligned practices can generate higher productivity and job satisfaction. The study also highlights the importance of leadership behaviors that support communal values, especially in the Indonesian context. Overall, this research contributes to the growing literature on strategic human resource management by offering empirical insights relevant to Southeast Asian enterprises. It emphasizes the need for integrated and context-sensitive HR practices to enhance employee outcomes in service-based industries.